2021
DOI: 10.1186/s12879-021-06368-1
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus infection among men who have sex with men and transgender women living with or at risk for HIV: a cross sectional study in Abuja and Lagos, Nigeria

Abstract: Background Despite the development of a safe and efficacious hepatitis B vaccine in 1982, the hepatitis B virus (HBV) remains a public health burden in sub-Saharan Africa. Due to shared risk factors for virus acquisition, men who have sex with men (MSM) and transgender women (TGW) living with HIV are at increased risk of HBV. We estimated the prevalence of HBV and associated factors for MSM and TGW living with or without HIV in Nigeria. Methods Sin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 41 publications
1
19
1
Order By: Relevance
“…Finally, ten studies [ 2 , 18 26 ] were entered into the analysis. Out of these articles, eight studies [ 2 , 18 22 , 24 , 26 ] reported the prevalence of HBV, and eight studies [ 2 , 18 20 , 22 , 23 , 25 , 26 ] reported HCV prevalence in transgender and LGBT people (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, ten studies [ 2 , 18 26 ] were entered into the analysis. Out of these articles, eight studies [ 2 , 18 22 , 24 , 26 ] reported the prevalence of HBV, and eight studies [ 2 , 18 20 , 22 , 23 , 25 , 26 ] reported HCV prevalence in transgender and LGBT people (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of all studies, two [ 18 , 19 ] had been conducted in the LGBT community (Total sample size = 2150), and eight [ 2 , 20 26 ] in the transgender community (Total sample size = 4273). Seven studies were conducted with cross-sectional design in Argentina [ 2 ], The Republic of Dominican [ 18 ], Spain [ 19 ], the United States [ 24 ], Nigeria [ 25 ], and Indonesia [ 26 ]; in contrast, three ones had been retrospectively conducted in Pakistan [ 21 ], Italy [ 20 ], and the United States [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HBV is endemic in some communities of MSM and transgender women (e.g. in Papua New Guinea 150 and Nigeria 151 ), and providing reliable healthcare for these groups is challenging. Access to care for MSM, bisexual and transgender communities may be further complicated in countries where legislation prohibits same-sex relationships.…”
Section: The Role Of Gendermentioning
confidence: 99%
“…HBV is endemic in MSM and transgender women (e.g. in Papua New Guinea 149 and Nigeria 150 ), but these groups may be hard to reach for screening, surveillance and treatment. High rates of drug and alcohol misuse may both increase the risk of exposure to infection with blood-borne viruses, and present barriers to interaction with healthcare services, as well as being associated with vaccine hesitancy in some populations 151 .…”
Section: The Role Of Gendermentioning
confidence: 99%